ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DINAS DAERAH (SIADINDA) PADA SEKRETARIAT DAERAH PROVINSI DAERAH KALIMANTAN BARAT - B51109107, Iis Nurhayati (Jurnal KIAFE, 2013)
Regional Office of Accounting Information Systems (SIADINDA) is an application used to aid financial management areas used by employees of the Secretariat of West Kalimantan Province. The purpose of this study was to determine the extent of implementation of the Regional Office of Accounting Information Systems (SIADINDA) in West Kalimantan Provincial Secretariat. This study was conducted with descriptive methods. Descriptive method as an activity that involves collecting data in order to test or answer any questions concerning the state of the running time of a subject of research. Data collection techniques using observation techniques, library research, documentary studies and questionnaires. The results showed that the respondents gave a good response, it means that the implementation of the application SIADINDA already performing well. Acceptance of the use of the technology itself to be well received by the user (user) which is visible from the high interest in using this application. The number of positive responses regarding the usefulness of the technology itself, the ease of use and the high frequency of use of these applications in their work indicates that the application is very useful and very helpful in their work. Keywords: Accounting Information Systems, SIADINDA, application